Comparison of fasting and non‐fasting patients receiving intravenous (IV) sedation. (21st September 2017) - Besi, E.; Besi, C.; Lees, R.; Morrison, A.; O'Connor, N.
Abstract: Aim: In 2015 the Intercollegiate Advisory Committee for Sedation in Dentistry published a national standard for the provision of conscious sedation in dentistry. This document highlighted the need for justification of the decision not to fast patients prior to administration of IV sedation. The aim of this case control study was to compare a fasting (F) and non‐fasting (NF) group of patients undergoing oral surgery procedures under IV sedation, and to assess for sedation related complications in both groups. Material and methods: A total of 228 patients were analysed, with 114 patients in each group. Results: Mean age was 33 years for the F group and 30.2 years for the NF group. The average midazolam dose was 5.11 mg for the F group and 5.72 for the NF group (pa = 0.03). The mean recovery time was: 38.53 min for the F group and 36.57 min for the NF group (pa = 0.14). Extra measures required included: supplemental oxygen for 5 patients in the F group and 6 patients in the NF group, Oral glucose was given during the recovery period to 6 patients in the F group. 1 patient in the F group was unable to be cannulated. Conclusions: Practicing minimal to moderate sedation in ASA 1 and 2 non‐fasting patients is safe and in our study appears to give less complications than the fasting patients.